The relation between adult weight gain, adipocyte volume and the metabolic profile at middle age - Verkouter, I; Noordam, R; Loh, NY; Willems van Dijk, K; Zock, PL; Mook-Kanamori, D; le Cessie, S; Rosendaal, FR; Karpe, F; Christodoulides, C; de Mutsert, R (Oxford University Press, 2021)
Purpose Weight gain during adulthood increases cardiometabolic disease risk, possibly through adipocyte hypertrophy. We aimed to study the specific metabolomic profile of adult weight gain, and to examine its association with adipocyte volume.